2022
DOI: 10.1186/s13098-022-00954-2
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome of obese postpartum women with and without previous gestational diabetes mellitus and the gut microbiota of their babies

Abstract: Background The incidence of gestational diabetes mellitus (GDM) is increasing worldwide, and has been associated with some changes in the gut microbiota. Studies have shown that the maternal gut microbiota pattern with hyperglycemia can be transmitted to the offspring. The study aimed to evaluate the gut microbiota of obese postpartum women with and without previous GDM and their offspring. Methods We evaluated a total of 84 puerperal women who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Setting aside the discussion about the presence or absence of the placental microbiome in the context of healthy pregnancy, studies have reported changes in the GM profile in pregnant women with gestational disorders such as preeclampsia (PE), gestational diabetes mellitus (GDM), fetal growth restriction (FGR), maternal obesity, among others. Supplementary Table 1 describes the profile of the microbiota in such gestational alterations (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Microbiome Alterations In Pregnancy Disordersmentioning
confidence: 99%
“…Setting aside the discussion about the presence or absence of the placental microbiome in the context of healthy pregnancy, studies have reported changes in the GM profile in pregnant women with gestational disorders such as preeclampsia (PE), gestational diabetes mellitus (GDM), fetal growth restriction (FGR), maternal obesity, among others. Supplementary Table 1 describes the profile of the microbiota in such gestational alterations (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Microbiome Alterations In Pregnancy Disordersmentioning
confidence: 99%